Monitoring in adaptive co-management: Toward a learning based approach - and Cundill, Georgina; Fabricius, Christo (Journal of Environmental Management, 2009)
The recognition of complexity and uncertainty in natural resource management has lead to the development of a wealth of conceptual frameworks aimed at integrated assessment and complex systems monitoring. Relatively less attention has however been given to methodological approaches that might facilitate learning as part of the monitoring process. This paper reviews the monitoring literature relevant to adaptive co-management, with a focus on the synergies between existing monitoring frameworks, collaborative monitoring approaches and social learning. The paper discusses the role of monitoring in environmental management in general, and the challenges posed by scale and complexity when monitoring in adaptive co-management. Existing conceptual frameworks for monitoring relevant to adaptive co-management are reviewed, as are lessons from experiences with collaborative monitoring. The paper concludes by offering a methodological approach to monitoring that actively seeks to engender reflexive learning as a means to deal with uncertainty in natural resource management.
Keywords: Adaptive co-management; Collaborative monitoring; Complexity; Social learning